Evidence that the human cell cycle is a series of uncoupled, memoryless phases - Hui Xiao Chao; Randy I Fakhreddin; Hristo K Shimerov; Katarzyna M Kedziora; Rashmi J Kumar; Joanna Perez; Juanita C Limas; Gavin D Grant; Jeanette Gowen Cook; Gaorav P Gupta; Jeremy E Purvis (Molecular Systems Biology)
Abstract The cell cycle is canonically described as a series of four consecutive phases: G1, S, G2, and M. In single cells, the duration of each phase varies, but the quantitative laws that govern phase durations are not well understood. Using time‐lapse microscopy, we found that each phase duration follows an Erlang distribution and is statistically independent from other phases. We challenged this observation by perturbing phase durations through oncogene activation, inhibition of DNA synthesis, reduced temperature, and DNA damage. Despite large changes in durations in cell populations, phase durations remained uncoupled in individual cells. These results suggested that the independence of phase durations may arise from a large number of molecular factors that each exerts a minor influence on the rate of cell cycle progression. We tested this model by experimentally forcing phase coupling through inhibition of cyclin‐dependent kinase 2 (CDK2) or overexpression of cyclin D. Our work provides an explanation for the historical observation that phase durations are both inherited and independent and suggests how cell cycle progression may be altered in disease states.